Reactions of ferrate(VI) with iodide and hypoiodous acid: Kinetics, pathways, and implications for the fate of iodine during water treatment - Shin, J.; Von Gunten, U.; Reckhow, D.; Allard, Sebastien; Lee, Y. (American Chemical Society, 2018)
© 2018 American Chemical Society. Oxidative treatment of iodide-containing waters can form iodinated disinfection by-products (I-DBPs) that are more toxic than the regulated DBPs. To better understand the fate of iodine during water treatment with ferrate(VI), kinetics, products, and stoichiometries for the reactions of ferrate(VI) with iodide (I-) and hypoiodous acid (HOI) were determined. Ferrate(VI) showed considerable reactivities to both I-and HOI with higher reactivities at lower pH. Interestingly, the reaction of ferrate(VI) with HOI (k = 6.0×103M-1s-1at pH 9) was much faster than with I-(k = 5.6×10 M-1s-1at pH 9). The main reaction pathway during treatment of I--containing waters was the oxidation of I-to HOI and its further oxidation to IO3-by ferrate(VI). However, for pH > 9, the HOI disproportionation catalyzed by ferrate(VI) became an additional transformation pathway forming I-and IO3-. The reduction of HOI by hydrogen peroxide (k = 2.0×108M-1s-1for the reaction, HOI + HO2-? I-+ O2+ 2H+), the latter being produced from ferrate(VI) decomposition, also contributes to the I-regeneration in the pH range 9 - 11. A kinetic model was developed that could well simulate the fate of iodine in the ferrate(VI)-I-system. Overall, due to a rapid oxidation of I-to IO3-with short-lifetimes of HOI, ferrate(VI) oxidation appears to be a promising option for I-DBP mitigation during treatment of I--containing waters.